Examining the relationship between group work and students’ willingness to participate - Ragusa, Sarah R. (Kansas State University, 2010)
In this thesis study, the use of group work as an instructional strategy was assessed to determine the effect it has on students’ willingness to communicate, communication apprehension, and self-perceived competence. Students enrolled in a basic public speaking at a major Midwestern university completed Neer’s (1987) Classroom Apprehension about Participation Scale (CAPS) at the beginning of the semester and again four weeks later after being exposed to a treatment of group or no group. Results indicated students’ willingness to communicate and self-perceived competence increased over the four-week duration of the study regardless of treatment. However, a significant reduction of communication apprehension was seen in students using group work in their classrooms. Limitations and implications are discussed.
Keywords: classroom participation; group; willingness to communicate; self-perceived competence; communication apprehension; Education, Curriculum and Instruction (0727); Education, Secondary (0533); Speech Communication (0459)